The Employment Impact of the Provision of Public Health Insurance: A Further Examination of the Effect of the 2005 TennCare Contraction - Ham, John C.; Ueda, Ken (Journal of Labor Economics, 2021)
In a 2014 paper, Garthwaite, Gross, and Notowidigdo examined the employment impact of the 2005 TennCare contraction. We extend their approach in several directions. First, we use consistent Conley-Taber estimation. Second, we transform their estimates to make them comparable to previous work; the transformed effects have large confidence intervals. We estimate their models using several larger data sets in an attempt to get more precise estimates but find that the results can be quite different. We consider two modifications to account for a major disruption to coverage in 2002, and one of these reduces the differences in the results.